PENGARUH BAURAN PEMASARAN RUMAH MAKAN PONDOK GABUS LUKMAN BEKASI TERHADAP LOYALITAS MELALUI KEPUASAN KONSUMEN - Nana Danapriatna; Dede Khoirul Fikri; Ahya Kamilah; Purnama Putra; Ummi Khoiriyah (Jurnal Agribisnis Indonesia, 2024)
The restaurant and eatery industry has become one of the fastest growing sectors throughout the world, including in Indonesia. One of the restaurants that plays an important role in the food industry in Bekasi City is the Pondok Gabus Lukman Restaurant. However, in facing increasingly fierce competition, Pondok Gabus Lukman restaurant needs to continue to innovate in marketing strategies to maintain and increase market share and build loyalty through strong consumer satisfaction. The purpose of this study was to find out how the characteristics of customer satisfaction and loyalty influence the marketing mix at the Pondok Gabus Lukman restaurant. The method used in this study is a quantitative method with sampling carried out in this study is convenience sampling, namely the presence of screening in advance, namely consumers who visit more than once. The analysis methods used are structural equation models, customer satisfaction index, and customer loyalty index. The results showed that the dimensions of the marketing mix (product, price and place) had a significant effect on customer satisfaction and loyalty, while the dimensions of the marketing mix (promotion, process, people/actors and physical evidence) had no significant effect on customer satisfaction and loyalty. The level of customer satisfaction at Pondok Gabus Lukman Restaurant is in the satisfied category with a value of 76.86%, and the level of consumer loyalty is in the very loyal category with a value of 88.43%. This shows that the influence of the marketing mix of Pondok Gabus Lukman Restaurant has a good influence on loyalty through customer satisfaction.